KONSTRUKSI KURIKULUM CINTA DALAM PENDIDIKAN AGAMA ISLAM: SINTESIS TAFSIR KONTEKSTUAL DAN MODERASI BERAGAMA DALAM PEMBELAJARAN - Mohammad Firmansyah; Sonia Isna Suratin; Munawarah; Muzawir Munawarsyah; Hasri Nur Azizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Religious Education faces the challenges of increasing exclusivism, intolerance, and radicalism, often rooted in a textual and less contextual understanding of religion. This situation demands a reconstruction of the Islamic Religious Education curriculum that is not only oriented towards the transfer of normative knowledge, but also towards the internalization of the values of compassion (love), humanity, and religious moderation. This study aims to analyze and formulate the construction of a love curriculum in Islamic Religious Education through a synthesis of contextual Qur'anic interpretations and the principles of religious moderation in learning. This study uses a qualitative approach with a literature study method. Data collection techniques are carried out through the search and analysis of primary and secondary sources in the form of tafsir books, books, and relevant scientific journal articles. Data analysis includes data reduction, data presentation, and drawing conclusions. Data validity is maintained through source and theory triangulation techniques. The results of the study indicate that the love curriculum in Islamic Religious Education can be constructed by emphasizing the values of mercy, justice, tolerance, and respect for diversity as the foundation of learning. The integration of contextual interpretation and religious moderation can provide humanistic, inclusive, and transformative Islamic Religious Education learning, thereby contributing to the formation of moderate-minded students oriented toward social peace.